2020
DOI: 10.1002/cbic.201900749
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous and Universal Detection of Various Targets with a Dual‐Step Transduced Toehold Switch Sensor

Abstract: Figure 3. Detectionoft hrombin. A) Schematic representationo fS Dt ransduction (Step I) for thrombin detection.B inding of the thrombin to the Blocker to release TP1. B) 12 %native PAGE analysis of hybridization between Blocker and TP1 with and withoutt hrombin. Lane Mt olane 3: ladder,TP1, Blocker and TP1,Blocker,TP1, and thrombin. C) Specificityc haracterization with ab ar graph representing endpoint detection at 2hcolor reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…The plot of intensity against the complex concentration over a 2-h interval obtained a sigmoidal fit with a steep rise between 10 nM and 100 nM (Section S4, Supplementary File S7). This showed that the model is sensitive to changes in the concentration of the trigger miRNA biomarker in the range of interest, satisfying a necessary biosensor property [ 25 , [55] , [56] , [57] , [58] , [59] , [60] ]. A similar trend of sigmoidal kinetics was observed for the hsa-miR-20a-5p biomarker over a complex concentration range of 100 nM and 1 μM (Supplementary File S7).…”
Section: Resultsmentioning
confidence: 99%
“…The plot of intensity against the complex concentration over a 2-h interval obtained a sigmoidal fit with a steep rise between 10 nM and 100 nM (Section S4, Supplementary File S7). This showed that the model is sensitive to changes in the concentration of the trigger miRNA biomarker in the range of interest, satisfying a necessary biosensor property [ 25 , [55] , [56] , [57] , [58] , [59] , [60] ]. A similar trend of sigmoidal kinetics was observed for the hsa-miR-20a-5p biomarker over a complex concentration range of 100 nM and 1 μM (Supplementary File S7).…”
Section: Resultsmentioning
confidence: 99%